2021
DOI: 10.1016/j.jcot.2021.04.012
|View full text |Cite|
|
Sign up to set email alerts
|

Surgical management of the acute severely infected diabetic foot – The ‘infected diabetic foot attack’. An instructional review

Abstract: Diabetic Foot Infection (DFI), in its severest form the acute infected 'diabetic foot attack', is a limb and life threatening condition if untreated. Acute infection may lead to tissue necrosis and rapid spread through tissue planes, in the patient with poorly controlled diabetes facilitated by the host status. A combination of soft tissue infection and osteomyelitis may co-exist, in particular if chronic osteomyelitis serves as a persistent source for recurrence of soft tissue infection. This "diabetic foot a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
13
0
1
Order By: Relevance
“…Internal fixation predominates in our series, because of a number of mid- and forefoot cases, where external fixation or ring fixation is technically challenging. Our experience in diabetic foot reconstruction and limb salvage 4 supports internal fixation, whereas external fixation was deemed unsuitable by some patients, thus leading to only a small group of patients (n = 3) with definitive external fixation.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Internal fixation predominates in our series, because of a number of mid- and forefoot cases, where external fixation or ring fixation is technically challenging. Our experience in diabetic foot reconstruction and limb salvage 4 supports internal fixation, whereas external fixation was deemed unsuitable by some patients, thus leading to only a small group of patients (n = 3) with definitive external fixation.…”
Section: Discussionmentioning
confidence: 84%
“…Our definitive surgical protocol, and index surgery for this study, involved further debridement as described above of potentially infected scar tissues, multiple biopsies (at least n=5 for microbiology and n=1 histology) as either part of a staged or definitive process. 4,7 All bone voids were measured intraoperatively in 3 dimensions once bony debridement and biopsies were completed. Voids were classified for containment and size; the former was identified as a cavity that would allow the graft to be placed into.…”
Section: Definitive Surgical Treatment and Void Measurementmentioning
confidence: 99%
“…Therefore, although these patients can be saved with a simple treatment, they usually end up with organ amputation. [ 14 ] In our study, we found that the patients who underwent emergency surgery due to DFA had applied to an average of two hospitals before applying to our facility. In addition, the high amputation rate of 69.2% was attributed to the fact that the patients were not referred to the appropriate facility, and cases that required emergency surgery were not detected in previous centers.…”
Section: Discussionmentioning
confidence: 95%
“…DFA is one of the most devastating presentations of diabetic foot disease, presents as an acute inflammation associated with rapid progressive necrosis, without timely intervention can rapidly progress to limb and life-threatening complications [ 6 ]. This can be an entirely new presentation or sudden deterioration of a diabetic foot ulcer, ischemia, or both.…”
Section: Discussionmentioning
confidence: 99%